Gluing na autogenous fragmente of a superior central incisor in a pediatric dental patient - Case report (Research, Society and Development, 2024)
The aesthetic and functional rehabilitation of fractured teeth at the cervical level is always a challenge for Dentistry. When the fragment remains intact and in perfect adaptation with the remaining tooth, gluing the fragment presents itself as a conservative and minimally invasive alternative for the recovery of fractured teeth. The study aimed to report the treatment for non-complex coronary fracture in the middle third, without pulp involvement, in the upper central incisor. A 10-year-old female patient attended the dental clinic at Centro Universitário Unifacid Wyden accompanied by her guardian, reporting a fracture of the upper central incisor (tooth 21) following a domestic accident suffered just over a week ago. After initial clinical and radiographic evaluation and assessment of the viability of the fragment brought by the patient, the proposed treatment was gluing the fragment to the tooth using flow resin. Given the clinical case presented, it can be concluded that due to advances in adhesive dentistry, the dental fragment bonding technique provides a satisfactory aesthetic and functional result for the patient.